Joe Bell [videorecording (DVD)] - Wahlberg, Mark, 1971-; Miller, Reid; Britton, Connie; Jenkins, Maxwell; Sinise, Gary (Vertical Entertainment, 2021)
Mark Wahlberg plays the rough-edged Oregon-based father who pays tribute to his gay teenage son Jadin by embarking on a walk across America to speak his heart to heartland adults and students about the potential terrifying high costs of bullying.